Community-acquired pneumonia in children: what's new?. Issue 10 (20th September 2011) - Thomson, Anne; Harris, Michael
Abstract : The community-acquired pneumonia in children guidelines have just been updated with new evidence on incidence, aetiology and management. This guidance should improve patient care.